PENGEMBANGAN MOBILE WEB, TERHADAP WEBSITE BPS PROVINSI SUMUT UNTUK MEGELOLA BUKU TAMU DALAM PELAYANAN - Yusfahmi; Ahmad Taufik Al Afkari Siahaan (ADISAM PUBLISHER, 2023)
This research details the mobile web development process aimed at optimizing the Central Bureau of Statistics (BPS) website to increase the effectiveness of guest book management in a service context. Through an in-depth analysis of user needs and existing processes, this research views the need for a mobile web-based solution to increase accessibility and responsiveness in recording and managing guest information. By utilizing responsive web technology, this research aims to make it easier for users to interact with the BPS platform, contributing to improving service quality and administrative efficiency. In this context it also discusses aspects of security and system integration ensuring the sustainability and reliability of the implemented solutions. It is hoped that the findings from this research can provide guidance for similar further development and improve the performance of guest book management within the BPS environment